Influencia de las relaciones interpersonales en el clima laboral de los colaboradores de la corporación tank's 105 servicios generales s.r.l. - trujillo: 2015 - Vasquez Chavez, Milagros Giahaida (2015)
This research has as its main purpose explain the influence of interpersonal relationships in the work environment at the collaborators of the CORPORACIÓN TANK'S 105 GENERAL SERVICES S. R. L. - Trujillo: 2015. It has been considered the type of applied research, on the basis of an explanatory design, and the sample consisted of 44 collaborators, with which work by applying the methods and techniques of quantitative and qualitative research. That goal was fulfilled with the results found in the qualitative and quantitative study. The results show us that in the CORPORACIÓN TANK'S 105 GENERAL SERVICES S. R. L. - Trujillo, is dominated by a poor communication between coworkers generating internal conflicts. In addition, it shows a lack of leadership and distrust what generates generates absenteeism and lack of team work as an expression of an inadequate labor climate. It is important that we be clear about the relevance of this study, considering that the interpersonal relations and the labor climate are fundamental to the collaborators contribute in the production and productivity of the company. Finally we believe that it is necessary to establish proposals for change toward the appropriate labor climate and interpersonal relationships with the purpose that the partners meet their objectives and goals.